MENGUJI ASAS DROIT DE SUITE DALAM JAMINAN FIDUSIA - I Made Sarjana; Desak Putu Dewi Kasih; I Gusti Ayu Kartika (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The principle of droit de suite is one of the most important principles in the law of guarantee,especially in fiduciary security. The principle implies that the rights of the creditor as therecipient of the fiduciary objects continue to follow the object of guarantee, wherever theobject is, to guarantee the repayment of the debts of the debitor. The rights which are ownedby the creditor as the recipient of fiduciary security in the principle seem to be absolute, butin fact if it is related to de practice, the principle of droit de suite has certain limitations.The limitations of this principle is whon it is faced with higher interest, the individual rightsowned by the recipient of fiduciary must succumb, as in the case of illegal logging, whichonce was decided to test the Forestry Law by the Constitutional Court (Case DecisionNumber 012/PUU-III/2005). Although the State can perform fiduciary deprivation of theobject which is used for committing illegal logging, but from the aspect of material criminallaw, it cannot be done immediately to destroy the object of guarantee, since object of thefiduciary collateral, is not considered a dangerous thing. Whereas, from the legal aspects ofcriminal procedure, if the case has been decided, then there is a duty of the State to returnthe object of fiduciary to those who own it.From the aspect of civil law, the creditor as recipient of fiduciary who feel harmed as aresult of illegal logging practices may have standing to sue for damages under Article 1365of Burgerljik Wetboek. The provision is used, because the act of illegal logging is an actagainst the law and there are losses caused to the recipient of fiduciary.